Uncovering an emerging policy direction for Australian energy and future fuels using a “participatory decision-making” framework - Kambo, Amrita; Kannampuzha, Leo; Arratia-Solar, Andrea; Witt, Katherine (Frontiers in Sustainable Energy Policy, 2024)
Introduction -An online deliberative engagement process was undertaken with members of the general public to understand what they value or would like to change about the energy system, within the broader context of decarbonizing Australia's energy networks, identifying a role for future fuels (hydrogen and biogas). Citizens developed a set of principles that could guide Australia's path towards a low-carbon energy future, reflecting on expectations they place upon energy transition. Next, citizens' principles were shared with policy-makers in government and policy-influencers from the energy industry using an online interactive workshop.Methods -This study analyses policy-makers and -influencers response to citizens' guiding principles using the 'diamond of participatory decision-making' framework for analysis. Convergence and divergence in diverse, complex and rich views across cohorts and implications thereupon energy policy were identified.Results -Although considerable alignment between multi-stakeholders' views was noted, key areas of divergence, or what is called the 'groan zone' were easily identified in relation to social and environmental justice issues. This groan zone highlights the struggles that energy policy-makers face -the need to listen and respond to citizens' voices, vs. the need for practical and workable policies that also support overarching government or industry objectives.Discussion -Policy making when the views of different stakeholders align is relatively straightforward. However, this is not the case where the expectations diverge. More creative measures will be needed to address divergent views and expectations whilst maintaining procedural fairness, in this case, using democratic deliberative engagement processes. While the use of deliberative processes is gaining momentum worldwide, particularly concerning climate change and energy transition policies, this paper also highlights the benefits of conducting a robust post facto analysis of the content of the processes. Areas of alignment, where policy can be made and implemented relatively easily without contention are identified. Other areas (such as making electrification mandatory) might be more complex or have unwanted negative social and environmental justice effects. Overall, this paper bridges an analytical gap between 'expectation studies' and participatory research. By borrowing terminology from a participatory research framework we sharpen the concepts in 'expectation studies' from a consensus, inclusion and diversity standpoint..